DOCUMENTARY REGISTRATION OF OPERATIONS WITH LAND RESOURCES IN THE CONDITIONS OF FUNCTIONING OF THE MARKET OF AGRICULTURAL LANDS (INNOVATIVE ECONOMY, 2020)
Bincharovska T.A. DOCUMENTARY REGISTRATION OF OPERATIONS WITH LAND RESOURCES IN THE CONDITIONS OF FUNCTIONING OF THE MARKET OF AGRICULTURAL LANDSPurpose. The aim of the article is the formation of a methodology for integrated documentary provision of movement of land resources at agricultural enterprises. The following tasks are formulated to achieve the set goal: to develop and substantiate a holistic methodical apparatus capable of documenting the documentary provision of land resources at the enterprises; to offer their own original documents; to develop a scheme of documentary design that will allow more thoroughly and thoroughly study the object of research.Methodology of research. General scientific and special methods of research are used in the course of the research, in particular: methods of analogy, generalization and comparison – for the theoretical generalization of the essence and documentary reflection of the land resources; abstract and logical approach and grouping – to determine the methodology of land registry accounting and documentary reflection.Findings. The problems of documentary registration of operations with agricultural land plots have been identified and covered. The analysis of scientific opinions of domestic scientists on the documentary reflection of land resources is carried out. The normative and legal base, which regulates accounting of land resources at agricultural enterprises, is analyzed. Initial and consolidated documents are proposed that will provide users with reliable and complete data.Originality. Documentary provision of operations with agricultural land resources is offered, taking into account all their specific features.Practical value. The obtained results of the research contribute to obtaining scientific information on agricultural land resources and increase its analytical capacity.Key words: land resources; documentation; accounting of land; agricultural land
Keywords: Key words; land resources; documentation; accounting of land; agricultural land